Characterization of Cell Envelope Multiple Mutants of Brucella ovis and Assessment in Mice of Their Vaccine Potential - Sidhu-Muñoz, Rebeca Singh; Sancho, Pilar; Cloeckaert, Axel; Zygmunt, Michel Stanislas; de Miguel, María Jesús; Tejedor, Carmen; Vizcaíno, Nieves (Frontiers in Microbiology, 2018)
Brucella ovis is a non-zoonotic Brucella species lacking specific vaccine. It presents a narrow host range, a unique biology relative to other Brucella species, and important distinct surface properties. To increase our knowledge on its peculiar surface and virulence features, and seeking to develop a specific vaccine, multiple mutants for nine relevant cell-envelope-related genes were investigated. Mutants lacking Omp10 plus Omp19 could not be obtained, suggesting that at least one of these lipoproteins is required for viability. A similar result was obtained for the double deletion of omp31 and omp25 that encode two major surface proteins. Conversely, the absence of major Omp25c (proved essential for internalization in HeLa cells) together with Omp25 or Omp31 was tolerated by the bacterium. Although showing important in vitro and in vivo defects, the Δomp10Δomp31Δomp25c mutant was obtained, demonstrating that B. ovis PA survives to the simultaneous absence of Omp10 and four out seven proteins of the Omp25/Omp31 family (i.e., Omp31, Omp25c, Omp25b, and Omp31b, the two latter naturally absent in B. ovis). Three multiple mutants were selected for a detailed analysis of virulence in the mouse model. The Δomp31Δcgs and Δomp10Δomp31Δomp25c mutants were highly attenuated when inoculated at 106 colony forming units/mouse but they established a persistent infection when the infection dose was increased 100-fold. The Δomp10ΔugpBΔomp31 mutant showed a similar behavior until week 3 post-infection but was then totally cleared from spleen. Accordingly, it was retained as vaccine candidate for mice protection assays. When compared to classical B. melitensis Rev1 heterologous vaccine, the triple mutant induced limited splenomegaly, a significantly higher antibody response against whole B. ovis PA cells, an equivalent memory cellular response and, according to spleen colonization measurements, better protection against a challenge with virulent B. ovis PA. Therefore, it would be a good candidate to be evaluated in the natural host as a specific vaccine against B. ovis that would avoid the drawbacks of B. melitensis Rev1. In addition, the lack in this attenuated strain of Omp31, recognized as a highly immunogenic protein during B. ovis infection, would favor the differentiation between infected and vaccinated animals using Omp31 as diagnostic target.